2016
DOI: 10.1210/en.2015-2081
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysacharide Rapidly and Completely Suppresses AgRP Neuron-Mediated Food Intake in Male Mice

Abstract: Although Agouti-related peptide (AgRP) neurons play a key role in the regulation of food intake, their contribution to the anorexia caused by proinflammatory insults has yet to be identified. Using a combination of neuroanatomical and pharmacogenetics experiments, this study sought to investigate the importance of AgRP neurons and downstream targets in the anorexia caused by the peripheral administration of a moderate dose of lipopolysaccharide (LPS) (100 μg/kg, ip). First, in the C57/Bl6 mouse, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 85 publications
(93 reference statements)
2
23
0
Order By: Relevance
“…Liu et al showed that LPS may be acting on the downstream targets of the AgRP neurons as opposed to directly affecting this neuronal population (Liu et al, 2016). Sartin et al showed that cfos actually increased in AgRP neurons 6 hours after LPS injection while Sergeyev et al showed that NPY expression was unaffected 4 hours post-LPS injection (Sartin JL, 2008; Sergeyev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that LPS may be acting on the downstream targets of the AgRP neurons as opposed to directly affecting this neuronal population (Liu et al, 2016). Sartin et al showed that cfos actually increased in AgRP neurons 6 hours after LPS injection while Sergeyev et al showed that NPY expression was unaffected 4 hours post-LPS injection (Sartin JL, 2008; Sergeyev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies found no detectable changes in LPS-induced c-Fos expression in POMC neurons [Gautron et al, 2005; Liu et al, 2016]. Previous reports by our group and others have described no changes in POMC mRNA expression in the ARC of rats treated with LPS [Gautron et al, 2005; Borges et al, 2007].…”
Section: - Hypothalamic Control Of Food Intake During Inflammationmentioning
confidence: 92%
“…Activation of AgRP neurons rapidly stimulates vigorous feeding whereas its inhibition or ablation suppresses food consumption [Krashes et al, 2011, Liu et al, 2016]. Considering that central AgRP injection blunted the hypophagic effect of LPS [Sartin et al, 2008] it has been postulated that inflammatory hypophagia might be caused by lack of AgRP action.…”
Section: - Hypothalamic Control Of Food Intake During Inflammationmentioning
confidence: 99%
See 2 more Smart Citations